Modeling and investigation of combined darrieus and vane design vertical axis wind turbine / Farhan Ahmed Khammas - Khammas, Farhan Ahmed (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2017)
The main objectives of this project are ; to investigate the aerodynamic characteristics of proposed combined wind turbine for solving the self-starting problem while increasing the output power ; to increase the starting torque of the new design wind turbine by Increasing the drag factor ; reducing the negative torque produced by the frame for the combined wind turbine rotating in the opposite direction of the wind ; to fabricate a model of the combined Darrieus (as lift device) and Vane type (as drag device) wind turbine ; to compare proposed mathematical model with an experimental data of the combined wind turbine model using a wind tunnel.